Analysis of postural control and muscle function performance of older adults participating in a multicomponent exercise program in primary health care - Leonardo Araujo Vieira; Jean Leite da Cruz; Milena Razuk; Natalia Madalena Rinaldi (Brazilian Society of Geriatrics and Gerontology, 2022)
Objectives: This cross-sectional study aimed to investigate (1) postural control performance in different postural tasks and (2) muscle strength and power of the hip, knee, and ankle of active vs inactive older adults. Methods: The sample consisted of 61 healthy community-dwelling older adults, classified into 2 groups: active, consisting of participants of a multicomponent exercise program offered through the Exercise Orientation Service; and inactive. Participants were considered physically active/inactive in the past 3 months. Postural control was assessed using a force plate in 8 postural tasks. Muscle function was evaluated using an isokinetic dynamometer. T-tests were used to compare clinical characteristics between the groups. ANCOVA and MANCOVA were used to compare differences in variables of postural control and muscle function. Results: Active participants had higher levels of physical activity, clinical balance, and quality of life than inactive participants. The active group had lower values for area (center of pressure) than the inactive group under the following conditions: bipedal stance on an unstable surface with eyes open and with eyes closed, and semi-tandem stance on an unstable surface with eyes open. The active group showed greater muscle power, with higher mean power values for hip abduction and adduction, knee extension, and knee flexion and shorter time to peak torque for hip adduction and ankle dorsiflexion than the inactive group. Conclusions: Multicomponent exercise programs delivered in primary health care settings contributed to improving postural control and muscle power in this sample of older adults, which can potentially help prevent falls and improve quality of life.